Partnership of I-ACT for children (US) and European pediatric clinical trial networks to facilitate pediatric clinical trials - Degraeuwe, Eva; Hovinga, Collin; De Maré, Annelies; Fernandes, Ricardo M.; Heaton, Callie; Nuytinck, Lieve; Persijn, Laura; Raes, Ann; Vande Walle, Johan; Turner, Mark A. (Frontiers in Pediatrics, 2024)
Background/aims Due to a lack of standard pediatric prescribing information, medicines are often used in a dosage form or for an indication that has not been investigated in children. Pediatric clinical trial research networks aim to facilitate the timely availability of innovative drugs for children by developing standardized trial facilitation and conduct processes. This paper aims to assess the (pre)feasibility duration and characteristics of a US-sponsored clinical trial, in collaboration with I-ACT for Children, for distribution across European sites via European clinical research facilitation networks. Method A transatlantic partnership between the Belgian Pediatric Clinical Research Network (BPCRN,) and I-ACT for Children conducted feasibilities in Europe for industry-sponsored early-stage pharmacological clinical trials between 2019 and 2022. The collaboration recorded time to event for key elements of feasibility, influences on successful feasibility, and benefits of collaboration. Results Trials were conducted across 17 European countries with 202 participating hospital sites. The initial phase, the pre-feasibility questionnaire had a 70% response rate from 142 sites, and sites took a median 38 days (IQR 20 days) to complete the questionnaire for five trials. All responses underwent a quality control, addressing inaccuracies in site capabilities and recruitment. The first trial's CDA and feasibility questionnaire were completed in roughly 2 months for 7 countries. Time to completion was affected by precontracted sites, limited scope of studies, changes in timelines, COVID-related disruptions, and a learning curve for collaboration. Conclusion Collaboration between European collaborative national networks and US-network I-ACT for Children has supported site identification of global pediatric clinical trials. This illustrates one method for the importance of early engagement with sponsors and implementation of effective communication systems.